Konsep Dasar Penelitian Tindakan Kelas : Sebuah Pengantar dalam Metode Penelitian Pendidikan - Yulita Putri; Abid Nurhuda; Ali Anhar Syi'bul Huda (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2023)
One aspect that cannot be separated in research efforts is the determination of the methodology used during research, this is very important because it is related to measuring instruments, data collection tools, to data analysis used in a study. One of the many research methods that has developed over time is classroom action research. This article seeks to explore in-depth matters related to classroom action research or PTK. The research design used in the study of this article is to use a qualitative approach with a literature study method of literature relevant to the topic of study then descriptive data analysis. The results of the study reveal that classroom action research is a practical effort from teachers, practitioners, and other researchers to improve, improve quality, and evaluate learning in the classroom. The principles of PTK are carried out in a natural environment, self-awareness for performance improvement, the use of SWOT analysis can be done as a basis for action, and following the SMART principle in planning. The steps of PTK include the planning stage (including problem identification, problem cause analysis, problem formulation, and solution), implementation stage, observation stage, and reflection stage.